Penerapan Metode Balanced ScoreCard Sebagai Suatu Sistem Pengukuran Kinerja pada PT Dritama Brokerindo, Jakarta Timur - Haryadi Sarjono; Arko Pujadi; Henry Wono Wong (Binus Business Review, 2010)
This research was done in insurance company of PT Dritama Brokerindo, East Jakarta, by using Balanced Scorecard method, with four perpectives which measured, which are the finance perpective (financial statement), customer perpective (quizioner), perpective process internal business (quizioner) and in growth, and study perpective (quizioner). With total employees 18 employees people, serving company customer about almost 1500.Research method which used is descriptive method with research type is case study. data analyse Technique which used is using primary data processing, like : field study, interview, quizioner and also secondary data with data collecting from company which is in the form of financial statement year 2005 - 2008. Research result that, performance PT Dritama Brokerindo which during the time measured traditionally, the management not get clear information, and measured about non finansial aspect of company. Triedly apply system of performance measurement with Balanced Scorecard, got the comprehensive and more complete result about condition of company which in fact. Pursuant to result of research from entirety aspect, obtained a total score 110, or value three which shown Good Enough criterion.